Environmental Software Systems - Denzer, Ralf (Springer, 2015)
Due to increasing practical needs, software support of environmental protection and research tasks is growing in importance and scope. Software systems help to monitor basic data, to maintain and process relevant environmental information, to analyze gathered information and to carry out decision processes, which often have to take into account complex alternatives with various side effects. Therefore software is an important tool for the environmental domain. When the first software systems in the environmental domain grew - 10 to 15 years ag- users and developers were not really aware of the complexity these systems are carrying with themselves: complexity with respect to entities, tasks and procedures. I guess nobody may have figured out at that time that the environmental domain would ask for solutions which information science would not be able to provide and - in several cases - can not provide until today. Therefore environmental informatics - as we call it today - is also an important domain of computer science itself, because practical solutions need to deal with very complex, interdisciplinary, distributed, integrated, sometimes badly defined, user-centered decision processes. I doubt somebody will state that we are already capable of building such integrated systems for end users for reasonable cost on a broad range. The development of the first scientific community for environmental informatics started around 1985 in Germany, becoming a technical committee and working group of the German Computer Society in 1987.